An experimental assessment of methods to predict crack deflection at an interface. (August 2017) - Alam, Mahabub; Parmigiani, John P.; Kruzic, Jamie J.
Graphical abstract: Highlights: Experimental evaluation of transition angle for crack deflection vs. penetration at interface. Energy method based only on toughness ratio under-predicts the transition angle. Cohesive zone method predicts the transition angle more accurately. Abstract: Several criteria have been proposed to predict whether a crack will penetrate through, or deflect along, an interface between two linear elastic materials. Moreover, the different criteria predict different crack penetration/deflection behavior creating uncertainty about which method to choose. To help remove some of this uncertainty, the present study presents experimental results on the quasi-static penetration/deflection behavior of cracks incident to interfaces in polymethyl methacrylate (PMMA) with various incident angles. Interfaces were created by bonding PMMA sheets using two different solvents. By varying the incident angles of the cracks on the interfaces, the transition angle for the transition from crack penetration to deflection was determined to be ɸ tran  ≈ 80° for the stronger and tougher interfaces and ɸ tran  ≈ 85° for the weaker and less tough interfaces. Using an energy-based criterion based solely on the toughness ratio, much lower transition angles ( ɸ tran  = 47° and 57°) were predicted for the interfaces than were experimentally observed. In contrast, using a cohesive zone method (CZM) approach that incorporates both the strength and toughness ratios gave predicted transition angles much closer to those experimentally observed for both the stronger ( ɸ tran  = 73°) and weaker ( ɸ tran  = 80°) interfaces. Finally, an approach that only considers the normal strength ratio was examined and poor agreement was found between predictions and experiments for 90° indent angle samples. Overall, it was found that the CZM approach makes predictions of the crack penetration/deflection behavior that were closest to the experimental results of this study.